2011
DOI: 10.1093/intimm/dxq478
|View full text |Cite
|
Sign up to set email alerts
|

CCR6hiCD11cint B cells promote M-cell differentiation in Peyer's patch

Abstract: M cells are responsible for uptake of mucosal antigens in Peyer's patches (PPs). Differentiation of M cells is thought to be induced by interactions between follicle-associated epithelium and PP cells; however, it remains elusive what types of immune cells function as M-cell inducers. Here, we attempted to identify the cells that serve as an M-cell inducer in PP. We found that a unique B-cell subset characterized by CCR6(hi)CD11c(int) resided in the subepithelial dome (SED) in mouse PP. CCR6(hi)CD11c(int) B ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
80
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(88 citation statements)
references
References 26 publications
8
80
0
Order By: Relevance
“…In WT mice, as anticipated, dense CCL20-specific immunolabeling was detected exclusively in association with the FAE (Fig. 7A) (Kobayashi et al, 2013, Zhao et al, 2003, Ebisawa et al, 2011). Our analysis showed that c-Rel-deficiency did not significantly affect the magnitude and distribution of CCL20 protein or mRNA expression when compared to WT mice (Fig.…”
Section: Resultssupporting
confidence: 82%
“…In WT mice, as anticipated, dense CCL20-specific immunolabeling was detected exclusively in association with the FAE (Fig. 7A) (Kobayashi et al, 2013, Zhao et al, 2003, Ebisawa et al, 2011). Our analysis showed that c-Rel-deficiency did not significantly affect the magnitude and distribution of CCL20 protein or mRNA expression when compared to WT mice (Fig.…”
Section: Resultssupporting
confidence: 82%
“…M cells are specifically present in the FAE of GALTs and have a nonredundant role in antigen uptake and the induction of immune reactions 9,10,14 . Despite previous reports on the possible role of B cells in M cell development 34,35 , studies showed that the M cell number is not decreased even in B cell deficiency 36,37 , leaving the mechanism of M cell induction unclear. Mesenchymal stromal cells have attracted considerable attention as an important regulator of the immune system 8 , and this study shows that MCi cells, a subset of GALT-resident mesenchymal cells, control IgA responses against luminal microbes.…”
Section: Discussionmentioning
confidence: 82%
“…CD21 lo human B cells have been proposed by some investigators to be exhausted or anergic B cells [24, 2933]. Another study demonstrated that murine CCR6 hi CD11c int B cells were shown to promote M-cell differentiation in Peyer’s patches [34]. These data together provided an early indication that CD11c+ B cells, or their equivalents, are important in humans.…”
Section: Cd11c Expression In B Cellsmentioning
confidence: 96%